Facile fabrication and configuration design of Co3O4 porous acicular nanorod arrays on Ni foam for supercapacitors. (31st May 2018) - Jiang, Tongtong; Yang, Siyu; Bai, Zhiman; Dai, Peng; Yu, Xinxin; Wu, Mingzai; Hu, Haibo
Abstract: The configuration of electrode materials is of great significance to the performance of supercapacitors (SCs) because of its direct effects on specific surface area and electron transfer path. Given this, herein, a series of Co3 O4 hierarchical configurations composed of porous acicular nanorods are designedly synthesized on Ni foam with in-site self-organization method depending on the addition of NH4 F. In the absence of NH4 F, Co3 O4 nanorods self-assemble into porous urchin-like structure (PULS), while the introduction of NH4 F can induce the vertical growth of Co3 O4 acicular nanorods, forming porous acicular nanorod arrays (PANRAs). By simply tuning the concentration of NH4 F, the Co3 O4 PANRAs with different specific surface area can be obtained. As expected, Co3 O4 PANRAs electrode for SCs (using 1 mmol of NH4 F) exhibits high specific capacitance (1486 F g −1 at 1 A g −1 ) and excellent cycling stability (98.8% retention after 5000 continuous charge–discharge cycles), which are better than those of Co3 O4 PULS electrode (658.2 F g −1 at 1 A g −1, 90.4%). Corresponding solid-state symmetric SC achieves a high energy density of 48.63 Wh kg −1 at power density of 600 W kg −1 . Such superior performance is attributed to fast charge transfer kinetics, facile electron transport and ions diffusion rate resulting from porous array structure, indicating the importance of configuration design of electrode materials for high performance SCs.